The impact of lead-time uncertainty in product configuration. Issue 3 (1st February 2021) - Song, Qinyu; Ni, Yaodong; Ralescu, Dan A.
Abstract : Product configuration is widely practiced and is very effective when offering mass customisation production. This strategy assists manufacturers in understanding customers' preferences and demands, presenting product relevant rules, choosing alternative components and modules, and constructing theoretical models. However, the uncertainties (such as lead-time uncertainty) are not fully considered in the product configuration. To fill this gap, we develop an uncertain product configuration model based on uncertain lead-time and time-sensitive demand using uncertain programming. Another contribution is that we explored the interdependence between uncertain lead-time and outsourcing strategy. This uncertain mixed-integer programming is solved by using CPLEX 12.8. During a series of numerical experiments, we found that the profit and the sourcing strategies are sensitive to the uncertain lead-time and the outsourcing strategy helps companies reduce losses due to uncertainty.